Mobile phone applications and self‐management of diabetes: A systematic review with meta‐analysis, meta‐regression of 21 randomized trials and GRADE. Issue 8 (3rd May 2018) - Hou, Can; Xu, Qian; Diao, Sha; Hewitt, Jonathan; Li, Jiayuan; Carter, Ben
Abstract : We conducted a systematic review with meta‐analysis of randomized controlled trials that evaluated the effect of diabetes mobile phone applications. A total of 1550 participants from 21 studies were included. For type 1 diabetes, a significant 0.49% reduction in HbA1c was seen (95% CI, 0.04‐0.94; I 2  = 84%), with unexplained heterogeneity and a low GRADE of evidence. For type 2 diabetes, using diabetes apps was associated with a mean reduction of 0.57% (95% CI, 0.32‐0.82; I 2  = 77%). The results had severe heterogeneity that was explained by the frequency of HCP feedback. In studies with no HCP feedback, low frequency and high frequency HCP feedback, the mean reduction is 0.24% (95% CI, 0.02‐0.49; I 2  = 0%), 0.33% (95% CI, 0.07‐0.59; I 2  = 47%) and 1.12% (95% CI, 0.91‐1.32; I 2  = 0%), respectively, with a high GRADE of evidence. There is evidence that diabetes apps improve glycaemic control in type 1 diabetes patients. A reduction of 0.57% in HbA1c was found in type 2 diabetes patients. However, HCP functionality is important to achieve clinical effectiveness. Future studies are needed to explore the cost‐effectiveness of diabetes apps and the optimal intensity of HCP feedback.